Functional connectivity, behavioral and dopaminergic alterations 24 hours following acute exposure to synthetic bath salt drug methylenedioxypyrovalerone. (15th July 2018) - Colon-Perez, Luis M.; Pino, Jose A.; Saha, Kaustuv; Pompilus, Marjory; Kaplitz, Sherman; Choudhury, Nafisa; Jagnarine, Darin A.; Geste, Jean R.; Levin, Brandon A.; Wilks, Isaac; Setlow, Barry; Bruijnzeel, Adriaan W.; et al.
Abstract: Among cathinone drugs known as bath salts, methylenedioxypyrovalerone (MDPV) exerts its potent actions via the dopamine (DA) system, and at intoxicating doses may produce adverse behavioral effects. Previous work by our group suggests that prolonged alterations in correlated neural activity between cortical and striatal areas could underlie, at least in part, the adverse reactions to this bath salt drug. In the present study, we assessed the effect of acute MDPV administration on brain functional connectivity at 1 and 24 h in rats. Using graph theory metrics to assess in vivo brain functional network organization we observed that 24 h after MDPV administration there was an increased clustering coefficient, rich club index, and average path length. Increases in these metrics suggests that MDPV produces a prolonged pattern of correlated activity characterized by greater interactions between subsets of high degree nodes but a reduced interaction with regions outside this core subset. Further analysis revealed that the core set of nodes include prefrontal cortical, amygdala, hypothalamic, somatosensory and striatal areas. At the molecular level, MDPV downregulated the dopamine transporter (DAT) in striatum and produced a shift in its subcellular distribution, an effect likely to involve rapid internalization at the membrane. These new findings suggest that potent binding of MDPV to DAT may trigger internalization and a prolonged alteration in homeostatic regulation of DA and functional brain network reorganization. We propose that the observed MDPV-induced network reorganization and DAergic changes may contribute to previously reported adverse behavioral responses to MDPV. Highlights: In rats, MDPV produced striatal dopaminergic, behavioral and functional connectivity effects lasting at least 24 hours. Functional connectivity increased between prefrontal cortical, amygdala, hypothalamic, somatosensory and striatal areas. MDPV altered the subcellular distribution of the striatal dopamine transporter, possibly via internalization. While the rewarding effects of MDPV wanes by 24 hours, we observed that social interaction was reduced.